Identifikasi Awal Perbedaan Karakter Morfofisiologi Antar Empat Kultivar Kopi Arabika - Dani Dani; Dewi Nur Rokhmah; Dibyo Pranowo (Pusat Penelitian dan Pengembangan Perkebunan, 2019)
Arabica coffee is a perennial crop hence it has a long selection cycle. Therefore, efforts to shorten the selection process is necessary, such as at seedling stage. This study aims to identify morpho-physiological characters variability among Arabica coffee cultivars at seedling stage. The experiment was conducted at Pakuwon Experimental Garden of Indonesian Industrial and Beverage Crops Research Institute, Sukabumi, from January to October 2017. Seeds collected from open pollinated trees of four arabica coffee cultivars (Ateng Super, P88, Gayo 1, and Gayo 2) were then sown on seedbed and newly-emerged cotyledonous seedlings were transferred immediately into polyethylene bag (polybag). Seedlings were arranged in randomized complete block with 5 replications, each consisted of 10 seedlings of each cultivar. Morpho-physiological characters observed and analyzed were shoot (plant height, lateral shoot formation, number of internodes, internode length, stem diameter, shoot’s dry weight); leaves (number of leaves, leaf length, leaf width, L/W ratio, leaf area, stomata density , chlorophyll content); and root (root length, number of primary roots, root volume, root’s dry weight, root/shoot ratio). The result showed value of genetic coefficient of variation (GCV), phenotypic coefficient of variation (PCV), and broad sense heritability (h2bs) of plant height characters are classified as high, each of which is 21.66%; 23.66%; and 0.84, respectively. The characters of the stem length and leaf width showed high h2bs value (0.97 and 0.67 respectively), while the KKG and KKF values were classified as moderate (19.60% and 19.88%, respectively and 10.71% and 13.10%, respectively). Those three characters could be utilized as distincitive markers of the four Arabica coffee cultivars.